Historical Perspectives on Colorectal Trauma Management - Tyler, Joshua A.; Welling, David R. (Clinics in Colon and Rectal Surgery, 2018)
The authors discuss the history and evolution of management of traumatic wounds to the colon and rectum, summarizing early management parallel with the history of armed conflict followed by the increase in research and management interest by civilian centers in the post-Vietnam era. They explore the strong opinions of the early thought-leaders such as DeBakey and Ogilvie, detailing factors that may have impacted their views. The current literature on optimal management of both colon and rectal trauma is reviewed, including the contentious debate over which patients may benefit from diversion. Current organ injury staging and clinical practice guidelines are also reviewed, as well as lessons learned by the U.S. military in recent conflicts in Iraq and Afghanistan. Understanding of the evolution of colon and rectal trauma management, as well as the current literature, will help surgeons in their decision-making and management of these challenging injuries.
Keywords: colon; rectum; trauma; injury; management; combat; military; diversion